Accountability in Islamic Social Enterprises (ISEs) from Stakeholders’ Perspective - Iqmal Hisham Kamaruddin, Muhammad; Md Auzair, Sofiah; Aini Muhamed, Nurul (International Journal of Engineering and Technology, 2018)
Accountability and non-profit sector is not a strange issue. As it has wider stakeholders as compared to other sectors, abuse, misappropriate and fraud cases frequently remark the â€˜dark sideâ€™ of non-profit sector. Plus, with the introduction of Social Enterprise (SE) concept that combine for both social and economic objectives in an entity, accountability issue become more tension as the complexity of the organization itself. Therefore, this study aims to examine accountability from stakeholdersâ€™ perspective, focusing on Islamic Social Enterprises (ISEs) in Malaysia. A questionnaire survey was utilized in this study and 50 ISEsâ€™ stakeholders from various stakeholders groups are contributed in this study. Based on findings, it can be said that all three accountability dimensions, which are accountability for input, accountability for output and accountability for procedural have significantly contribute toward accountability in ISEs in Malaysia. Ironically, most ISEsâ€™ stakeholders are still believed that current accountability practices in ISEs in Malaysia is still in moderate level. Â